2020
DOI: 10.1042/bsr20201501
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 induces connective tissue growth factor expression and promotes peritoneal metastasis of gastric cancer

Abstract: Transforming Growth Factor-β1 (TGF-β1) is involved in human cancer development and progression. Nonetheless, the role of TGF-β1 as regards peritoneal metastasis of gastric cancer has not been completely characterized. In this study, we investigated the exact role of TGF-β1 on peritoneal metastasis of gastric cancer. The results indicated that human peritoneal mesothelial cells (HPMCs) exposed to TGF-β1 or serum free conditional medium (SF-CM) of SGC7901 which produced a large amount of TGF-β1 became exfoliated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…[43] In two studies, TGF-β inhibition significantly reduced the number of peritoneal nodules in tumors grown from SGC-7901 cells. [34,56] Another study showed the same effect in tumors grown from HSC-39 cells. [52] The effect of TGF-β on non-tumor cells Several studies investigated the effect of TGF-β addition on mesothelial cells, fibroblasts, endothelial cells and immune cells.…”
Section: The Effect Of Tgf-β On Metastasis In Vivomentioning
confidence: 76%
See 4 more Smart Citations
“…[43] In two studies, TGF-β inhibition significantly reduced the number of peritoneal nodules in tumors grown from SGC-7901 cells. [34,56] Another study showed the same effect in tumors grown from HSC-39 cells. [52] The effect of TGF-β on non-tumor cells Several studies investigated the effect of TGF-β addition on mesothelial cells, fibroblasts, endothelial cells and immune cells.…”
Section: The Effect Of Tgf-β On Metastasis In Vivomentioning
confidence: 76%
“…[43][44][45][46][47][48][49][50] Thirteen studies assessed adhesion to either a fibronectin membrane or peritoneal mesothelial cells. [34,43,46,[51][52][53][54][55][56][57][58][59][60] Additionally, 11 studies tested invasion capacity by allowing cells to migrate toward a serum gradient for an extended period of time. [36,37,[43][44][45][46][47][48] Green = increased apoptosis or decreased proliferation, Grey = no effect, Red = increased proliferation.…”
Section: Effect Of Tgf-β On Migration Adhesion and Invasion Capacities Of Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations